Gendered realities of GBV in Khayelitsha to Inform safety and security in urban planning and policy - Petersen, Ashleigh (School of Architecture, Planning and Geomatics, 2026)
Violence against women and gender minorities is a complex social phenomenon and can be affected by the relationship between the built environment and human behaviour. With the South African township of Khayelitsha in the 30 top hotspots for gender-based violence (GBV) globally, this dissertation aimed to analyse the response of organisations and urban policy to violence in Khayelitsha and tried to answer whether these efforts in any way addressed the needs of women and gender minorities regarding Gender-based Violence (GBV) (Maphanga, 2020). With the very high prevalence of GBV in Khayelitsha, the main research question asked: “how have lived experiences of women and gender minorities in Khayelitsha, regarding GBV, informed safety and security for urban planning and policy?” On the assumption that cities should provide safe and secure spaces, this dissertation asked: “does the built environment exacerbate GBV?”, “can gendered urban planning address GBV as an urban safety and security issue?”, and “can gender mainstreaming urban policy improve GBV in public spaces?”. Through a qualitative case study approach of Khayelitsha, I explored work done by Violence Prevention Through Urban Upgrading (VPUU) and urban policy documents. I additionally collected data through semi-structured interviews, indirect observations, and desk research. Ethical constraints limited the study in that vulnerable individuals were not interviewed, but individuals with experience of Khayelitsha's public spaces were interviewed. Findings revealed that women and gender minorities' experiences of GBV in Khayelitsha have poorly informed safety and security for urban planning and policy. Traditional solutions have poorly understood gendered spatial contexts, which caused inappropriate prevention methods for GBV. The research concluded with recommendations for safety and security urban planning and policy for GBV in Khayelitsha, thereby contributing to closing the gender gap in planning research in the Southern township context.